Parallel programming and concurrency with C# 10 and .NET 6 : a modern approach to building faster, more responsive, and asynchronous . NET applications using C# - Ashcraft, Alvin (Packt Publishing, Limited, 2022)
Leverage the latest parallel and concurrency features in .NET 6 when building your next application and explore the benefits and challenges of asynchrony, parallelism, and concurrency in .NET via practical examples Key Features Learn to implement parallel programming and handle concurrency in .NET efficiently Switch threads while debugging and learn how to monitor specific threads in Visual Studio Discover how to cancel tasks with callbacks, by polling, or by using a task with wait handles Book Description .NET has included managed threading capabilities since the beginning, but early techniques had inherent risks: memory leaks, thread synchronization issues, and deadlocks. This book will help you avoid those pitfalls and leverage the modern constructs available in .NET 6 and C# 10, while providing recommendations on patterns and best practices for parallelism and concurrency. Parallel, concurrent, and asynchronous programming are part of every .NET application today, and it becomes imperative for modern developers to understand how to effectively use these techniques. This book will teach intermediate-level .NET developers how to make their applications faster and more responsive with parallel programming and concurrency in .NET and C# with practical examples. The book starts with the essentials of multi-threaded .NET development and explores how the language and framework constructs have evolved along with .NET. You will later get to grips with the different options available today in .NET 6, followed by insights into best practices, debugging, and unit testing. By the end of this book, you will have a deep understanding of why, when, and how to employ parallelism and concurrency in any .NET application. What you will learn Prevent deadlocks and race conditions with managed threading Update Windows app UIs without causing exceptions Explore best practices for introducing asynchronous constructs to existing code Avoid pitfalls when introducing parallelism to your code Implement the producer-consumer pattern with Dataflow blocks Enforce data sorting when processing data in parallel and safely merge data from multiple sources Use concurrent collections that help synchronize data across threads Debug an everyday parallel app with the Parallel Stacks and Parallel Tasks windows Who this book is for This book is for beginner to intermediate-level .NET developers who want to employ the latest parallel and concurrency features in .NET when building their applications. Readers should have a solid understanding of the C# language and any version of the .NET Framework or .NET Core.